The Degree of Including Aesthetic Values in Social and National Education Textbook of Fourth Basic Grade in Jordan - Hassan, Salsabil Adeeb; Abu Sneina, Odeh Abdel-Gawad (Journal of Educational and Psychological Sciences, 2019)
The current study aimed to reveal the degree of including aesthetic values in social and national education textbook of the fourth basic grade in Jordan. The descriptive analytical approach was used. The sample of the study consisted of the social and national education book for the fourth grade that included the first and second parts, and the researcher used the intentional or purposive sample. The results of the study indicated the aesthetic values that should be included in the social and national education book for the fourth grade in Jordan, where it totalled to (21) aesthetic values. The results have also shown that the total frequency of the first semester was (52) implicitly with a percentage of (22.4%), and the total frequency of the first semester was (55) explicitly with a percentage of (23.7%), while the total frequency of the second semester was (77) implicitly with a percentage of (33.2%), and the total frequency of the second semester was (48) explicitly with a percentage of (20.7%). The study recommended that curriculum developers should include songs and music when modifying the experimental version of the social education book to include a set of elements, such as style, space, depth, and colour, as well as the need of educators and curriculum developers to put attractive drawings and exciting texts for the student in order to develop his or her aesthetic taste.
Keywords: degree; values; education; aesthetic; patriotism; fourth grade